Licit magic : the life and letters of al-Ṣaḥib born ʻAbbad (d. 385/995) - Pomerantz, Maurice A. (Islamic History and Civilization, 2017)
In Licit Magic: The Life and Letters of al-Ṣāḥib born ʿAbbād (d. 385/995) Maurice A. Pomerantz explores the biography and literary output of a major tenth-century Muslim statesman, literary patron, and intellectual. His nearly two-decade reign as vizier on behalf of two Buyid amirs was an important period for the flowering of Arabic letters, Muʿtazilī theology and Shīʿism in Western Iran. Making use of Ibn ʿAbbād's large corpus of letters ( rasāʾil ), Pomerantz explores the role that eloquence played in the conduct of administration, the maintenance of social networks of elites, and persuasion. Licit Magic argues that the eloquent expression that Ibn ʿAbbād displayed in his letters was central to his exercise of power.